Striking back at Striga - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Africa has 75 million hectares of land that can grow cereals, but two-thirds of it is now infested with Striga hermonthica. Other species of striga parasitise leguminous crops like cowpeas. Striga can cause crop losses as high as 85%. To turn the...